The Combination of Long-term Ketamine and Extinction Training Contributes to Fear Erasure by Bdnf Methylation - Ju, Ling-Sha; Yang, Jiao-Jiao; Lei, Lei; Xia, Jiang-Yan; Luo, Dan; Ji, Mu-Huo; Martynyuk, Anatoly E.; Yang, Jian-Jun (Frontiers in Cellular Neuroscience, 2017)
A combination of antidepressant drugs and psychotherapy exhibits more promising efficacy in treating fear disorders than either treatment alone, but underlying mechanisms of such treatments remain largely unknown. Here we investigated the role of DNA methylation of the brain-derived neurotrophic factor (Bdnf) gene in the therapeutic effects of ketamine in combination with extinction training in a mouse model of post-traumatic stress disorder (PTSD) induced by inescapable electric foot shocks (IFS). Male mice received ketamine for 22 consecutive days starting 1 h after the IFS (long-term ketamine treatment) or 2 h prior to the extinction training on days 15 and 16 after the IFS (short-term ketamine treatment). The open field and elevated plus maze tests were conducted on days 18 and 20. The spontaneous recovery and fear renewal tests were performed on day 23. Mice, subjected to IFS, exhibited anxiety-like behavior and fear relapse, accompanied by the increased levels of DNA methyltransferases, hyper-methylation of Bdnf gene, and decreased BDNF mRNA expression in the medial prefrontal cortex and hippocampus. Long-term treatment with ketamine combined with extinction training alleviated the IFS-induced abnormalities. These results suggest that long-term ketamine treatment in combination with extinction training may ameliorate fear relapse in the murine model of PTSD, at least in part, by normalizing DNA methylation of Bdnf gene.